Statistical Analysis of Changes in Physical and Chemical Parameters and Cooking Quality of Rice with a Combination of Temperature Treatment and Amylose Content During Storage - Febriana Intan Permata Hati; Joko Nugroho Wahyu Karyadi; Nursigit Bintoro (The University of Lampung, 2023)
Rice is one of the staple foods produced in Indonesia. One of the postharvest processes experienced by rice is storage. During the storage process, rice changes cooking quality, physical and physicochemical qualities. This research aims to analyze changes in cooking, physical and physicochemical qualities of Indonesian rice varieties. The rice varieties used, namely Sintanur, Ciherang, and IR 42 were stored at storage room temperatures of 30˚C, 20˚C, and 10˚C. Rice taken from farmers was stored for 4 months and changes were measured for parameters of water content, color (chroma, hue, whiteness), amylose, elongation ratio, gel consistency, alkali spreading value (ASV), water absorption, and texture profile (packability, hardness, cohesiveness, extrudability, chewiness). The results showed that the lowest water content was at sintanur which was stored at 10 ˚C, namely 3.09% wb, elongation, and ASV increased with the highest final value at sintanur 30 ˚C, namely 2.07 and 4.45, the consistency of the gel decreased in the first week then stable in the following week, on the other hand, water absorption increased at the beginning of storage and did not change much until the end of storage. Statistical tests showed that there was an interaction between time*variety*temperature on the parameters of water content, whiteness, elongation ratio, water absorption, amylose, and chewiness. Based on the research results, it was found that several parameters did not interact with temperature, namely hue, packability, hardness, and extrudability. Keywords: Amylose content, Cooking quality of rice, Physical quality of rice, Rice storage